Indoor environmental factors associated with influenza transmission in mainland China between February and April 2023 - Nan Zhang; Shuyi Ji; Beidi Niu; Hua Qian; Yuguo Li; Hao Lei (Elsevier, 2024)
Background: The relaxation of strict COVID-19 control measures has led to a considerable increase in the number of influenza cases in 2023. This worrisome situation has posed a greater burden on public health and healthcare systems. Understanding environmental drivers of influenza epidemics can provide valuable insights for developing effective interventions. Methods: We conducted an online survey from April 13th to 14th, 2023 to investigate the incidence of influenza-like illness (ILI) and influenza A within the past two months. A total of 4916 valid questionnaires were collected in mainland China. The questionnaire explored the relationship between the spread of ILI/Influenza A and factors including personal attributes, living environment, indoor ventilation, and personal behaviours. Results: Out of the 4916 respondents, 1583 reported having ILI in the past two months, and among them, 456 were infected with influenza A. The multivariate logistic regression analysis revealed significant associations with a lower likelihood of reporting ILI for the following variables: being female (Adjusted OR (aOR) = 0.834), having bedroom ventilation time exceeding 12 hours (aOR = 0.782), wearing masks in public places (aOR = 0.646), and using surgical masks (aOR = 1.417). Conversely, variables associated with an increased risk of ILI included larger household size (>4: aOR = 2.405), presence of odours in the bathroom (aOR = 1.163), commuting by bus (aOR = 1.265), longer indoor stay during weekdays (>18 h: aOR = 1.969), and a history of COVID-19 infection (aOR = 1.459). Furthermore, handwashing after toileting (aOR = 0.694) was associated with a lower reporting of influenza A. Conclusions: Our study innovatively examined the impact of personal and environmental factors on influenza transmission. These observational findings can provide a scientific guidance for preventive measures against influenza.